Optimization of vehicle pulse index parameters based on validated vehicle-occupant finite element model - Abdul Samad, M. S.; Mohd Nor, M. K.; Abdul Majid, M. M.; Abu Kassim, K. K. (Taylor&francis, 2023)
Vehicle safety performance is important to reduce occupant injuries during accidents. In general, vehicle manufacturers are utilizing analytical models to predict the vehicle passive safety performance during the early design stage. The two popular methods are the Occupant Limit Criterion (OLC) and Vehicle Pulse Index (VPI). In this paper, new VPI parameters are proposed to predict the driver 3 ms chest acceleration of Hybrid III 50th percentile (H350) in B-segment vehicle subjected to generic crash load cases. A good correlation between the newly optimized VPI parameters with the measured 3 ms chest acceleration is observed in this work. More refinement can be further included to improve the robustness of the new proposed parameters by adding more sampling data